Structural, vibrational, and electrical study of compressed BiTeBr - Sans, J. A.; Manjon, F. J.; Pereira, A. L. J.; Vilaplana, R.; Gomis, O.; Segura, A.; Munoz, A.; Rodriguez-Hernandez, P.; Popescu, C.; Drašar, Čestmír; Ruleová, Pavlína (American Physical Society, 2016)
Compresed BiTeBr has been studied from a joint experimental and theoretical perspective. Room-temperature x-ray diffraction, Raman scattering, and transport measurements at high pressures have been performed in this layered semiconductor and interpreted with the help of ab initio calculations. A reversible first-order phase transition has been observed above 6-7 GPa, but changes in structural, vibrational, and electrical properties have also been noted near 2 GPa. Structural and vibrational changes are likely due to the hardening of interlayer forces rather than to a second-order isostructural phase transition while electrical changes are mainly attributed to changes in the electron mobility. The possibility of a pressure-induced electronic topological transition and of a pressure-induced quantum topological phase transition in BiTeBr and other bismuth tellurohalides, like BiTeI, is also discussed.
imitace dynamiky molekul
Keywords: initio molecular-dynamics; total-energy calculations; augmented-wave method; basis-set; pressure; transition; plane; phase; semiconductors; emergence; initio molekulové dynamiky; Celkové energetické výpočty; Metoda rozšířené vlna; Základem-set; tlak; přechod; letadlo; fáze; polovodiče; vznik